Reproductive compatibility and morphological characterization of local populations of the larval endoparasitoid Pseudapanteles dignus in Argentina - Vallina, Consuelo (2020)
In hymenopteran parasitoids, isolated geographic populations can show morphological variation and reproductive incompatibility that may lead to failures in biological control programs when they are intended to be used as biocontrol agents. Through a classical morphometric approach we confirm the specific identity of three local populations of the larval arrhenotokous endoparasitoid Pseudapanteles dignus (Muesebeck) (Hymenoptera: Braconidae) of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), from three main tomato producing areas of Argentina. Moreover, we examined reproductive compatibility by outcrossing the three populations. Morphometric differences among P. dignus biotypes were found but no evidences of mating incompatibility among them existed. This laboratory study contributes with relevant information to the original description of the species P. dignus and has significant implications for T. absoluta biological control using this parasitoid in tomato crops from different regions of Argentina.